Exploring the association between suicidal thoughts, self-injury, and GLP-1 receptor agonists in weight loss treatments: Insights from pharmacovigilance measures and unmasking analysis - Amira Guirguis (European Neuropsychopharmacology, 2024)
IntroductionThe study addresses concerns about potential psychiatric side effects of Glucagon-like peptide-1 receptor agonists (GLP-1 RA).AimThe aim of this work was to analyse adverse drug reports (ADRs) from the Food and Drug Administration Adverse Events Reporting System (FAERS) using metformin and orlistat as comparators.MethodsDescriptive and pharmacovigilance disproportionality analyses was performed.ResultsA total of 209,354 ADRs were reported, including 59,300 serious cases. Of those, a total of 5378 psychiatric disorder cases, including 383 ‘serious’ cases related to selected ADRs were registered during 2005–2023. After unmasking, 271 cases where individual GLP-1 RA were implicated showing liraglutide (n = 90; Reported Odds Ratio (ROR) = 1.64), exenatide (n = 67; ROR = 0.80), semaglutide (n = 61; ROR = 2.03), dulaglutide (n = 45; ROR = 0.84), tirzepatide (n = 5; ROR = 1.76) and albiglutide (n = 2; ROR = 0.04). A greater association between these ADRs with metformin was observed, but not orlistat. With regards to selected preferred terms (PTs), 42 deaths including 13 completed suicides were recorded. Suicidal ideation was recorded in n = 236 cases for 6/7 GLP-1 RA (excluding lixisenatide).DiscussionSuicide/self-injury reports pertaining to semaglutide; tirzepatide; and liraglutide were characterised, although lower than metformin. It is postulated that rapid weight loss achieved with GLP-1 RA can trigger significant emotional, biological, and psychological responses, hence possibly impacting on suicidal and self-injurious ideations.ConclusionsWith the current pharmacovigilance approach, no causality link between suicidal ideation and use of any GLP-1 RA can be inferred. There is a need for further research and vigilance in GLP-1 RA prescribing, particularly in patients with co-existing psychiatric disorders.